Some Aspects of Sport and Sports Injuries in Ancient Rome - Kranjc, Janez (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
The author discusses some of the characteristics of sport in ancient Rome. In addition to recreational sports, he also mentions the spectacles that entertained Roman audiences as well as competitions in Greek athletic disciplines. While there were no major competitions in recreational sports, which mainly included ball games, other sports were marked by intense competition. In particular, chariot races and gladiatorial combats, and probably also athletic competitions, were mass spectacles that attracted huge crowds. In relation to combat sports, the author also discusses the issue of liability for injuries that occurred during competitions and training. In general, Roman lawyers rejected claims for damages if the injury was not caused by a violation of the rules. As long as the competition or training took place according to the rules and at the designated location, it was considered that the perpetrator could not be held liable for damages in the event of injury.